COMPLEX THINKING AND THE PROJECT PORTFOLIO IN PHILANTHROPIC HEALTH INSTITUTIONS - Paulo de Sousa Silva, João; Giacomassi, Rafael (Health and Society, 2025)
Working within a highly volatile scenario and subject to numerous interrelationships, institutions in the philanthropic healthcare sector must navigate both the efficiency and flexibility, characteristic of private entities, while retaining the focus on the purpose of social equity, typical of public entities. This dichotomy renders the implementation of a project portfolio a significant challenge. It was in recognition of the inherent features of this scenario that this research grounded its development in complex thinking. This allowed for learning rather than the imposition of pre-determinism, and critical reflection instead of hypothesis testing. Given the systemic nature of this research, the Soft System Methodology was chosen as the approach. Conducted within a philanthropic institution dedicated to oncological treatment, this unique case study originated from comprehending the organizational context through the lens of complex thinking to formulate an action plan centered on the implementation and management of a project portfolio. The outcomes demonstrated that steering this process guided by complex thinking enables greater flexibility and agility in project selection, as well as enhanced integration among stakeholders, along with reduced maturation time in the initiation and planning phases. On the other hand, this adoption opens discussions about the challenges of employing a holistic line of thought within a culture rooted predominantly in the positivist paradigm.